Defining Antisemitism in Francophone Canada: The Plamondon Trials of 1913–1914 - Anctil, Pierre (Canadian Jewish Studies / Études juives canadiennes, 2026)
The study of antisemitism in twentieth-century Canada has recently attracted considerable scholarly attention, especially given the country’s poor record in welcoming Jewish refugees fleeing Nazi Germany before and during the Second World War. This article argues that scholarship in this domain has tended to oversimplify the differences that existed between Anglophone and Francophone Canada in this respect, often ignoring elements of religious doctrine that kept Catholics and Protestants relatively apart in their understanding of Jews and Judaism. To better define the frame of reference of Francophone Roman Catholics, the author examines the documentation produced during the 1913–1914 Plamondon defamation trials in Quebec City. These trials offer a unique opportunity to better understand the inner workings of antisemitism within a French Canadian elitist milieu, independently of other forms of Judeophobia that predominated in English Canada.